Which family capitals aid rural and urban first-generation college students in China to realise intergenerational mobility in higher education? - Cheng, S (2021)
With the growth of the gross enrolment rate in higher education in China, the number of college students whose parents have no higher education experience is also increasing. This group of students is known as the first generation of college students. This phenomenon challenges cultural reproduction theories’ view that it is difficult for children from disadvantaged family who lack the cultural capital to realise an intergenerational breakthrough in higher education. Many studies found that family capitals are the core factors to aid first-generation college students to realise such an intergenerational breakthrough. However, to date, numerous studies considered Chinese first-generation college students as rural students and ignored their first-generation urban counterparts. Furthermore, it is essential to establish the role of family capitals based on Chinese students’ experience. Therefore, this research aims to establish the family capitals aiding rural and urban first-generation college students to realise intergenerational breakthrough in higher education, and the differences as well as similarities in rural and urban family capitals.